Determinants of dividend payout The case of Algerian private banks - Nabila Allal; Billel BENILLES (Dirassat Journal Economic Issue, 2020)
The objective of this article is to study the determinants of dividend payout within Algerian private banks over the period 2011-2017. To do this, we used a regression method on panel data on a sample of eleven Algerian private banks. The results of this study reveal the significant and positive impact of the bank’s profitability, previous dividends, equity levels, debt, liquidity and growth on dividend distribution. On the other hand, there is a negative relationship between risk and dividend distribution.